Perceptions of Pharmacy and Other Health Professional Students toward Interprofessional Education - Ogbaghebriel, Azieb; AlHuwaidi, Jude; AlZeer, Raneem (Indian Journal of Pharmaceutical Education and Research, 2021)
Background: Interprofessional Education (IPE) equips students with a background for multidisciplinary collaboration in health care provision and its success could be influenced by students’ attitudes. Objectives: To assess the readiness and perceptions of pharmacy and other health professional students toward IPE. Methods: A survey was conducted on students of Pharmacy, Medicine, Nursing, Dentistry and Health and Rehabilitation Sciences (HRS) utilizing the 19-item instrument for assessing the Readiness for Interprofessional Learning Scale (RIPLS) with four subscales. Data analysis was done on individual items, the sub-scales and total scores using descriptive and inferential statistics. Results: Individual item scores were above 4 out of 5 for most of the RIPLS items except for negative professional identity and roles and responsibility. Overall total mean score was 76.40 ±10.30 out of 95, with no significant difference among the colleges. On the subscale of professional identity, Dentistry and Nursing scores were significantly lower. On attitudes towards roles of nurses and therapists, scores of Nursing and HRS showed significant disagreement with those of Medicine and Dentistry, but not with Pharmacy. Overall, only 28% of the participants had prior knowledge of IPE, with Pharmacy having relatively higher percentage (37.4%). There was no significant correlation of the RIPLS scores with either age or year of study. Conclusion: Overall, students’ attitude toward IPE was positive. Differences in perceptions of professional identity, roles and responsibilities among some professions require attention of educators since understanding of such attributes is vital for creating effective healthcare teams.
Keywords: Interprofessional education; Health professions; Pharmacy students; Middle East; Perceptions; Readiness